A study on hydrogen isotopes transport in a liquid metal GaInSn by plasma-driven permeation method. (August 2017) - Bi, Hailin; Hirooka, Yoshi; Yagi, Juro; Xu, Yue
Highlights: A technique of holding a liquid metal on a mesh sheet for plasma-driven permeation experiment has been developed. Hydrogen isotopes diffusivity and recombination coefficients for liquid GaInSn have been obtained. Hydrogen isotopes retention in liquid GaInSn are found to be low. Abstract: The application of liquid metals such as gallium, tin and lithium as plasma-facing materials is a potential means to resolve the technical issues associated with power exhausting and particle handing in magnetic fusion devices. GaInSn alloy with melting point of 10.5 °C, is employed as a modeling material to explore the plasma-driven permeation (PDP) method to study the hydrogen isotopes (hydrogen and deuterium) transport parameters in a liquid metal. Static liquid GaInSn membranes sitting on a mesh sheet are exposed to hydrogen/deuterium plasmas in the linear plasma device VEHICLE-1 with the temperature range of 280–496 °C. Hydrogen/deuterium diffusivity are obtained by fitting the time evolutions of permeation fluxes. The dynamic hydrogen/deuterium retention in the liquid GaInSn are found to be low (∼10 15 D/cm 3 ), which are consistent with the thermal desorption spectroscopy (TDS) measurement following plasma exposure. The hydrogen and deuterium transport parameters are found to be close to each other.